Cybersecurity as a public utility: A study in legal foundations and administrative organization - Nameer Ali Abdulwahab (International Journal of Law Research and Studies, 2026)
The digital revolution has brought about radical changes in the nature of the state’s functions and tools. Public services are no longer confined to traditional areas such as security, defense, health, and education, but have expanded to include cyberspace, which has become a primary arena for human and institutional activity. Information systems and digital infrastructure have become the backbone of public administration, the national economy, and essential services, making their protection vital to the stability and security of the state. In this context, cybersecurity emerges as a public function for which the state assumes responsibility to protect the digital space from increasing risks and threats, whether cyberattacks, data breaches, or disruptions to vital services. This has led to a reassessment of the legal nature of cybersecurity and the extent to which it can be considered a public utility subject to the rules of public law, requiring the state to regulate, manage, and ensure its continuity. The importance of this study is evident in several key aspects, most notably the vital role cybersecurity plays in protecting digital public facilities and services; the novelty of the concept of cybersecurity as a public utility and the complex legal and regulatory issues it raises; and the need for a legal framework that defines the nature of cybersecurity and the limits of state intervention in this field. This study aims to achieve a number of important objectives, the most important of which are: clarifying the concept of cybersecurity, its developmental paths, and its basic functions; analyzing the legal foundations that make cybersecurity a public utility; examining the distinctive characteristics of cybersecurity within the framework of public utility principles; and highlighting the administrative organization of cybersecurity and the role of competent authorities in its management. The central question of this study revolves around the extent to which cybersecurity can be considered a public utility, and what These are the legal and regulatory foundations that govern it. This study adopted a descriptive analytical approach by analyzing legal and regulatory texts related to cybersecurity and outlining its characteristics as a public utility. The deductive approach was also employed to derive general rules from the legal principles governing public utilities and apply them to the field of cybersecurity. In conclusion, the research yielded a set of findings indicating that cybersecurity is a modern public utility directly linked to the protection of the public digital system. The legal basis for cybersecurity rests on the constitution and legislation related to national security and data protection. Cybersecurity possesses the characteristics of a public utility in terms of continuity, public nature, and state oversight.